P056 IMPLEMENTING MASS CYTOMETRY AS A TOOL FOR INFLAMMATORY BOWEL DISEASE RESEARCH. (18th January 2018) - Tyler, Christopher; Rivera-Nieves, Jesus
Abstract: Background: An expanding range of therapeutics have been approved or are under development for IBD. However, objective readouts of treatment efficacy are still lacking, often relying on partially subjective clinical endpoints (CDAI). High-dimensional mass cytometry (CyTOF) combines flow cytometry with elemental mass spectrometry, allowing the simultaneous quantification of up to 40 surface and/or intracellular markers on a single cell basis. This technique presents a novel tool by which the therapeutic effects of drugs could be examined directly within the target tissue. Methods: Intestinal biopsies and peripheral blood were obtained from healthy individuals and from patients with active IBD undergoing various treatments. Immune cells were isolated from biopsies/blood and stained with a panel of 37 markers for analysis using CyTOF. Results: Optimized protocols were developed to allow for efficient implementation of mass cytometry into IBD studies, including freezing of biopsy samples (yields of viable cells >70% as compared with fresh biopsies), to allow for storage and shipping of clinical samples. Yields of CD45+ cells derived from healthy/inflamed colonic biopsies were similar (6x104 2x104), with significant increases and decreases in the proportion of CD4+ T and B cell populations, respectively (n>8/group, P<0.001) in inflamed samples. t-SNE and ClusterX analysis of the CD4+ T cell lineage identified 22 CD4+ subsets with differential abundance between healthy and inflamed tissue. In particular, increases in CD4+integrin β7+ cells were observed in inflamed tissue, alongside expression of CD69, CD127, CD161, PD-1, and CD49d. Discussion: CyTOF has the potential to identify distinct immune subsets involved in intestinal inflammation, allow for evaluation of the effects of therapeutic agents, and ultimately highlight distinct immune subsets in peripheral blood which represent cellular biomarkers of clinical response to therapeutics.